Agama dalam kajian sosiologi - Al-Mudzaky, Tibyan Arwani (Maliki Interdisciplinary Journal, 2024)
Religion has been a significant social phenomenon in various societies and cultures throughout human history. Sociology as a science that studies social interaction, social structure, and is interested in the role of religion in shaping and influencing society. The origins of sociology will describe the development of the sociology of religion. 2 The elements contain anything that is the basic elements of a religion. Then, for the function of religion, we will discuss the role of religion in overcoming a problem that arises in society.